Thermoeconomic optimization of a solar-assisted supercritical CO2 Brayton cycle, organic Rankine cycle and multi-effect distillation system - Khademi, Mohammad; Ahmadi, Abolfazl; Dashti, Reza; Shirmohammadi, Reza (Energy reports, 2022)
In this paper, the simulation and optimization of a combined supercritical carbon dioxide Brayton cycle, an organic Rankine cycle and multi-effect distillation system driven by solar energy have been applied for power and freshwater generation. In this cycle, the solar collector, the central receiver reflected the sun’s light by heliostats, enters the storage system and then enters the fluid stream according to the amount of heat required to initiate the cycle. The working fluid of solar receiver is a mixture of the 60% NaNO3 and 40% KNO3, supercritical carbon dioxide is working fluid of the Brayton cycle and R600 is the working fluid of the organic Rankine cycle. The innovation of this article is using power and fresh water cycle without fuel consumption (with solar system and storage tanks). The simulation of this combined cycle was carried out by engineering equation solver software and energy and exergy efficiency changes in terms of different parameters are obtained. Then, a multi objective optimization of this system considering exergy efficiency and cost of system as objective functions is performed by genetic algorithm in Matlab software. Decision variables of the whole cycles are including Compressor inlet temperature, Turbine inlet temperature, Number of MED effect, The temperature of the water fed the desalination, Evaporator pinch point, Mass flow (Critical Carbon Dioxide), Turbine inlet pressure, Compressor inlet pressure and Pressure drop. The two objective functions optimization including exergy and economic parameters of this cycle is carried out for achieving reduction of electricity generation cost and increase of the exergy efficiency. The results of this optimization showed, the maximum exergy efficiency of this combined system is 61.78% and the minimum cost of electricity production is 0.2617 $/kWh. In this regard, the multiple effect distillation system produces 530.9 KgS freshwater in 15 stages.